Discourse, Structure and Linguistic Choice The Theory and Applications of Molecular Sememics - Price Caldwell, T. (Studies in Linguistics and Philosophy, 2018)
This volume presents eight papers and a draft monograph by T. Price Caldwell on topics in linguistics, semiotics and philosophy of language. From the beginning of his professional career onwards, Caldwell wrote short fiction and poetry, and he taught English literature. The relevance to these of philosophy of language, semiotics and certain areas of linguistics increasingly caught his interest. This book presents the fruits of this later work. Of the papers included here, two are abstract and theoretical, focusing on linguistic methodology and Caldwell's overarching views on the nature of meaning-in-context. His position here, which he called Molecular Sememics, echoes early Structuralism and Functionalism, but addresses shortfalls in each. Two other papers apply the method and theory to topics within semantics and pragmatics, including especially the structuring of discourse. The remaining four papers connect Caldwell's theoretical insights to his life-long interests in fiction and pedagogy. The monograph - which Caldwell was left unfinished due to illness - aims to present as a single intellectual package the theory and the applications.